Religious Education as a Vehicle of Cultural Integration: Qualitative Data from Secondary Education Theology Teachers - Chatzivasiloglou, Emmeleia (Greek Journal of Religious Education (GjRE), 2025)
This article explores the contribution of Religious Education to the integration of second-generation immigrant students in Secondary Education. The aim of the study is to highlight the subject’s role as a space for intercultural dialogue and the cultivation of values that foster social cohesion. The research employed a qualitative methodology through semi-structured interviews with Secondary Education theology teachers during the 2024–2025 school year. The thematic analysis of the data revealed that Religious Education can serve as a bridge for integration, promoting respect, solidarity, and tolerance, although challenges remain, such as stereotypes and the lack of appropriate teaching material. The findings emphasize the need for teacher training and the strengthening of interdisciplinary collaborations. Suggestions for further research and practical applications are discussed, with a focus on promoting social justice and educational equity.